Moyamoya Disease: An uncommon cause of young stroke - Khan, Sharif Uddin; Rahman, Kazi Mohibur; Hoque, Md Azharul; Alam, Md Badrul; Siddiqui, Md Mahmudur Rahman; Wahab, Luna; Haque, Badrul; Daisy, Selina; Mohammad, Quazi Deen; Faruque, Md; Islam, AEM Mazharul (Journal of Armed Forces Medical College, Bangladesh, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> doi:10.3329/jafmc.v4i2.1843 JAFMC Bangladesh Vol.4(2) 2008 33-37